GAYA HIDUP KONSUMTIF MAHASISWI BIDIKMISI ILMU ADMINISTRASI NEGARA UNIVERSITAS TEUKU UMAR - Melia Safitri; Arfriani Maifizar; Nurkhalis Nurkhalis (Jurnal Society : Pengamat Perubahan Sosial, 2022)
Consumptive lifestyle has become a common thing among students’ bidikmisi, so the student’s bidikmisi can not allocate their bidikmisi to the needs of the lecture. As for the formulation at the University of Teuku Umar what are the factors that affect the consumptive lifestyle on this study is to find out how the lifestyle of students bidikmisi Science of the State Administration and the factors that affect the consumptive lifestyle on a students State Administration Science at the University of Teuku Umar. This research uses qualitative methods and descriptive determination of informants by purposive sampling with data collection techniques through observation, interview, and documentation.            The results showed that the lifestyle of a student bidikmisi State Administrasi science at the University of Teuku Umar That the student is indeed classified as consumptive because are fond of buying goods in the market at elite boutiques and Mall, spending money and time hanging out in the café, eating at fast food restaurants and consuming branded goods or just the consumption of the symbolic value. While the factors that affect the consumptive of globalization, technology as well as the influence of advertisement either directly or indirectly.